A Facile Strategy for Self‐Healing Polyurethanes Containing Multiple Metal–Ligand Bonds. Issue 6 (4th January 2018) - Wang, Zhenhua; Xie, Chuan; Yu, Changjiang; Fei, Guoxia; Wang, Zhanhua; Xia, Hesheng
Abstract: A metal–ligand crosslinked internal self‐healing polyurethane is developed using low‐cost and commercially available compounds. The mechanical, photoluminescent, and self‐healing properties can be governed by incorporating multiple metal–ligand crosslinks with weak and strong coordination bonds and varying the metal ion. In‐situ attenuated total reflectance Fourier transform infrared spectroscopy reveals that the metal–ligand bond is cleaved during the damage process while metal ion is still coordinated with the ligand by stronger metal–pyridyl interaction. The multiple metal–ligand coordination facilitates the crosslinks to be fully reformed during the repairing process, leading to the superior self‐healing property. Abstract : Multiple metal–ligand bonds are incorporated into polyurethanes, allowing for superior mechanical and self‐healing properties.